The socio-spatial distribution of walkable environments in urban scotland: A case study from Glasgow and Edinburgh - Anna Kenyon; Jamie Pearce (SSM: Population Health, 2019)
Increasingly, evidence shows that built environments (BEs) can encourage walking. Not only does walking have the potential to benefit health, it can also be used as a form of transport, reducing reliance on motorised transport and reducing CO2 emissions. However, little is known about the distribution of such features within urban environments. Furthermore, debate surrounds whether people living in areas with high deprivation face the ‘double jeopardy’ of high deprivation and environments that are unsupportive of walking.This study aims to address this knowledge gap by developing measures of the built environment considered to support walking and assessing and whether there is a relationship between these with area-level deprivation in urban Scotland. It also examines the geographic distribution of these measures in two of Scotland's biggest conurbations. Three aspects of the physical built environment considered to reflect Area Walking Potential (AWP) were created which are considered to show good walking environments, there were residential density, intersection density and destination accessibility, as well as an overall walkability index (a combination of the three measures). The results showed no evidence of deprivation amplification with higher concentrations of the AWP measures in more deprived areas. Those living in the least deprived areas having the lowest levels of the measures. However, spatial analysis showed unequal distribution of these measures, with concentrations of high AWP clustered together with lower AWP scores in peripheral areas. These results support the growing evidence base of unequal geographic distribution of AWP. These results matter for developing built environments to support walking because it is important to understand how existing patterns of AWP to target interventions appropriately. Awareness of associations between AWP and deprivation is important for policies aimed at ameliorating multi-level inequalities demonstrating where people are likely to be experiencing both low AWP and high deprivation. Keywords: Spatial inequalities, Area deprivation, Walkability, Socio-spatial, Geographic information systems, Urban scotland